Anton Heiller organist, composer, conductor - Planyavsky, Peter (Eastman studies in music, 2014)
Anton Heiller is one of the twentieth century's most renowned and influential organists. Born in 1923, Heiller was trained in Vienna and rose to prominence quickly, giving his first solo recital at the age of twenty-two. Before concentrating on the organ exclusively, he was a successful conductor of the symphonic repertoire, and from 1945 until his untimely death in 1979, he was professor for organ at the University of Music and Performing Arts in Vienna.His interpretations of Bach, which included registration and articulation, as well as a consideration of the theological underpinnings, would change the way Bach is played. Anton Heiller: Organist, Composer, Conductorprovides an assessment of Heiller's works and teaching, while also examining his complex personality, one torn between strong religious devotion and the world of artistry. Underlying this story here is also the story of church music and organ playing in central Europe in the decades after World War II, and of the then unique crossroads of organ cultures in mid-twentieth-century Europe. Peter Planyavsky was Anton Heiller's successor as an organ professor in Vienna, and Organist of St. Stephan's Cathedral in Vienna from 1969 through 2004. He is also a prolific composer, improviser, and conductor. The book is translated from the original German by Christa Rumsey, also a former student of Heiller